2002
DOI: 10.1096/fj.02-0074fje
|View full text |Cite
|
Sign up to set email alerts
|

SAGE transcript profiles of normal primary human hepatocytes expressing oncogenic hepatitis B virus X protein

Abstract: Hepatitis B virus (HBV) is a major risk factor for hepatocellular carcinoma (HCC). HBV encodes an oncogenic HBx gene that functions as a transcriptional coactivator of multiple cellular genes. To understand the role(s) of HBx in the early genesis of HCC, we systematically analyzed gene expression profiles by serial analysis of gene expression (SAGE) in freshly isolated human primary hepatocytes infected with a replication-defective adenovirus containing HBx. A total of 19,501 sequence tags (representing 1443 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 36 publications
6
21
0
Order By: Relevance
“…Comparative analysis of HBV-and HCV-associated HCC cell lines revealed that many ribosomal-related genes such as RPL family genes were up-regulated in HBV-associated HCC cell lines (HBVHCCs) in comparison to HCV-associated HCC cell lines (HCV-HCCs), suggesting the activation of protein translation in HBV-HCCs. This observation is consistent with the previous report that major classes of genes encoding ribosomal proteins were up-regulated by the HBX protein (19). In addition, genes involved in extracellular matrix and cytoskeletal organization, such as ANXA2, KRT8, CKAP4, KRT7 and CFL1, were shown to be up-regulated in HBV-HCCs, as well as genes such as K-ALPHA-1, ANXA1, ACTB, and ANXA5 in HCV-HCCs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Comparative analysis of HBV-and HCV-associated HCC cell lines revealed that many ribosomal-related genes such as RPL family genes were up-regulated in HBV-associated HCC cell lines (HBVHCCs) in comparison to HCV-associated HCC cell lines (HCV-HCCs), suggesting the activation of protein translation in HBV-HCCs. This observation is consistent with the previous report that major classes of genes encoding ribosomal proteins were up-regulated by the HBX protein (19). In addition, genes involved in extracellular matrix and cytoskeletal organization, such as ANXA2, KRT8, CKAP4, KRT7 and CFL1, were shown to be up-regulated in HBV-HCCs, as well as genes such as K-ALPHA-1, ANXA1, ACTB, and ANXA5 in HCV-HCCs.…”
Section: Discussionsupporting
confidence: 92%
“…The application of global approaches such as the collection of expressed sequence tags (ESTs), Serial Analysis of Gene Expression (SAGE) and microarray techniques have been shown to be useful in the analysis of complex biological phenomena, including human diseases (15,(17)(18)(19)(20)(21). Among these approaches, the expressed sequence tags (ESTs) generated by the single-pass sequencing of randomly selected cDNA clones from cDNA libraries have been used to identify novel genes (22).…”
Section: Introductionmentioning
confidence: 99%
“…In SAGE-based analysis of the transcriptional profiles on normal primary human hepatocytes expressing HBX protein by transient transfection, Wu et al observed that the up-regulated genes fell into three categories, including genes encoding ribosomal protein, transcription factors with the zinc finger motif, multiple proteasome subunits, ubiquitin, and ubiquitinassociated proteins (33). Some of these changes showed a pattern similar to that found in our transgenic mouse model expressing the HBX protein, although the genes with significant changes are different.…”
Section: Resultsmentioning
confidence: 99%
“…The results of nuclear location of ubiquitin and its relativity with IκB-α indicated the proteolysis of IκB-α was processed in tumor cell nuclei. Of course, another likelihood was that transcription of ubiquitin would be promoted after NF-κB activation [27] . There is no relativity between ubiquitin and HBx, so whether the proteolysis of HBx passes through non-ubiquitin pathway or not remains to be determined.…”
Section: Discussionmentioning
confidence: 99%